The competitive action of non-profit legal entities (and the freedom to carry out economic activities) - Pazos Hayashida, Javier Mihail (2024)
This paper examines whether nonprofit organizations can engage in economic activities not directly related to altruistic or charitable objectives within the legal framework of Peru, thereby challenging the traditional perception that these entities should be limited to charitable activities.It explores the intersection between profit motive and economic activity, emphasizing the private autonomy that allows these organizations to define their own goals and activities.In summary, this study highlights how these organizations contribute to development through their active participation in the market, highlighting their integral role in the contemporary economy and society.